Battery

By adjusting the type and proportion of solvents in the electrolyte, the wetting and kinetics of the silicon negative electrode are improved, and the design of the shell and connecting plate are combined, the problems of slow charging speed and temperature rise of lithium-ion batteries are solved, achieving high energy density, good fast charging performance and low temperature rise.

CN119725681APending Publication Date: 2025-03-28ZHEJIANG COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411916278.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing lithium-ion batteries wait for a long time when charging, resulting in a decrease in user travel efficiency. The charging speed and charging efficiency of the battery are limited by the internal resistance of the battery, resulting in problems such as temperature rise and capacity attenuation.

Method used

By adjusting the type and proportion of solvents in the electrolyte, the wetting and kinetics of the silicon negative electrode are improved, and the design of the shell and connecting sheet are combined to reduce the temperature rise of the battery.

Benefits of technology

It realizes the advantages of high energy density, good fast charging performance and low temperature rise of the battery, extends the cycle life of the battery and improves safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725681A_ABST
    Figure CN119725681A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium batteries, and provides a battery, which comprises: at least one battery cell monomer, which comprises a positive tab and a negative tab; the connecting sheet comprises a connecting sheet body, a pole connecting part arranged at one end of the connecting sheet body and a tab connecting part arranged on the connecting sheet body; the shell is used for packaging the battery cell monomers and the connecting sheets; each battery cell monomer comprises a positive plate, a diaphragm and a negative plate which are laminated; the negative plate comprises a negative active material, and the negative active material comprises a silicon-based material; in the negative electrode active material, the mass ratio w of the silicon element is 1%-40%; the battery comprises an electrolyte, wherein the electrolyte comprises a cyclic organic matter and a linear organic matter; the mass ratio of the linear organic matter to the cyclic organic matter is recorded as a, and a is larger than or equal to 1.2 and smaller than or equal to 5. The battery has the advantages of high energy density, good fast charging performance and low temperature rise.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a battery. Background Art

[0002] Traditional battery charging technology is relatively safe and friendly to the long life cycle of batteries. However, with the rapid development of new energy vehicles, the waiting time for battery charging is long, resulting in reduced travel efficiency for users and "energy replenishment anxiety". "Energy replenishment anxiety" has become an urgent problem that needs to be solved in the current development of new energy vehicles. To solve "energy replenishment anxiety", it is necessary to increase the energy density of the battery and increase the charging speed at the same time. However, in practical applications, the charging speed and efficiency of the battery are often limited by the internal resistance of the battery. Battery internal resistance refers to the resistance caused by internal materials, structures and other factors of the battery during operation. It has an important influence on the fast charging performance of the battery. Under the condition of high-rate rapid charging and discharging, a large amount of heat will be generated at the battery's pole ear, resulting in a high temperature rise of the battery, accelerating the side reactions inside the battery, and then causing the battery capacity to decay faster. Summary of the invention

[0003] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and to provide a battery, which adjusts the type and proportion of solvents in the electrolyte, improves the wettability and dynamics of the silicon negative electrode, and at the same time combines the design of the shell and the connecting piece to reduce the temperature rise of the battery, so that the battery has the advantages of high energy density, good fast charging performance and low temperature rise.

[0004] In order to achieve the above object, the present invention provides a battery in a first aspect, comprising:

[0005] At least one battery cell, wherein the battery cell comprises a positive electrode tab and a negative electrode tab;

[0006] The connecting piece comprises a connecting piece body, a pole connecting portion arranged at one end of the connecting piece body, and a pole ear connecting portion arranged on the connecting piece body; the pole connecting portion is protrudingly arranged on the connecting piece body;

[0007] A shell, encapsulating the battery cell and the connecting piece;

[0008] The battery cell comprises a stacked positive electrode sheet, a separator and a negative electrode sheet; the negative electrode sheet comprises a negative electrode active material, and the negative electrode active material comprises a silicon-based material; in the negative electrode active material, the mass proportion w of silicon element is 1%-40%;

[0009] The battery also includes an electrolyte, the electrolyte includes cyclic organic matter and linear organic matter; the cyclic organic matter includes C1-C8 cyclic carbonate; the linear organic matter includes C1-C8 linear carbonate and / or C1-C8 linear carboxylate; the mass ratio of the linear organic matter to the cyclic organic matter is denoted as a, and a satisfies: 1.2≤a≤5.

[0010] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0011] (1) The battery provided by the present invention improves the wettability and dynamics of the silicon negative electrode by designing the electrolyte and adjusting the type and proportion of the solvent in the electrolyte. At the same time, the temperature rise of the battery is reduced by matching the design of the shell and the connecting piece, so that the battery has the advantages of high energy density, good fast charging performance and low temperature rise;

[0012] (2) The battery provided by the present invention further suppresses the gas production of the battery by controlling the content of the cyclic carbonate in the electrolyte. At the same time, the cyclic carbonate has good film-forming performance on the silicon negative electrode, thereby improving the cycle performance of the battery.

[0013] (3) The battery provided by the present invention further improves the kinetics of lithium salt and the thermal stability of electrolyte and reduces side reactions by adjusting the type and content of lithium salt in electrolyte, and at the same time adjusts the thickness of the tab single layer to reduce heat generation at the tab.

[0014] (4) The battery provided by the present invention further regulates the interface stability of the negative electrode by regulating the fluorine-containing additives and sulfur-containing additives in the electrolyte that are beneficial to the formation of the negative electrode film, and at the same time improves the cycle performance of the battery by adjusting the OI value of the negative electrode.

[0015] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Shown is a first structural schematic diagram of a square shell battery.

[0017] Figure 2 Shown is a second structural schematic diagram of a square shell battery.

[0018] Figure 3 Shown is a schematic diagram of the first cross-sectional structure of a square shell battery.

[0019] Figure 4Shown is a schematic diagram of the second cross-sectional structure of a square shell battery.

[0020] Figure 5 Shown is a schematic diagram of the cross-sectional structure of the connecting piece.

[0021] Figure 6 Shown is a schematic diagram of the structure of a battery cell.

[0022] Reference numerals: 1-housing; 11-top cover; 12-positive pole; 13-negative pole; 14-liquid injection hole; 2-cell; 21-positive pole ear; 23-negative pole ear; 3-connecting piece; 31-positive pole connecting piece; 311-first pole ear connecting part; 312-first pole column connecting part; 313-fusing area; 32-negative pole connecting piece; 321-second pole ear connecting part; 322-second pole column connecting part; DETAILED DESCRIPTION

[0023] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0024] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0025] In the present invention, the terms "battery", "laminated battery", "lithium battery", "lithium-ion battery" and "lithium-ion secondary battery" all have the same meaning and refer to lithium-ion secondary batteries, which generally include battery cells (such as positive electrodes, negative electrodes and separators), containers (shells) for accommodating the battery cells, and electrolytes.

[0026] The present invention provides a battery, comprising:

[0027] At least one battery cell, wherein the battery cell comprises a positive electrode tab and a negative electrode tab;

[0028] A connecting piece, comprising a connecting piece body, a pole connecting portion arranged at one end of the connecting piece body, and a pole lug connecting portion arranged on the connecting piece body; the pole connecting portion is protrudingly arranged on the connecting piece body; optionally, the connecting piece body, the pole connecting portion and the pole lug connecting portion are integrally formed;

[0029] A shell, encapsulating the battery cell and the connecting piece;

[0030] The battery cell comprises a stacked positive electrode sheet, a separator and a negative electrode sheet; the negative electrode sheet comprises a negative electrode active material, and the negative electrode active material comprises a silicon-based material; in the negative electrode active material, the mass proportion w of silicon element is 1%-40%;

[0031] The battery also includes an electrolyte, the electrolyte includes cyclic organic matter and linear organic matter; the cyclic organic matter includes cyclic carbonate; the linear organic matter includes C1-C8 linear carbonate and / or C1-C8 linear carboxylate; the mass ratio of the linear organic matter to the cyclic organic matter is denoted as a, and a satisfies: 1.2≤a≤5.

[0032] In some embodiments, the housing includes metallic aluminum or an alloy containing aluminum.

[0033] In the present invention, adding silicon-based materials to the negative electrode activity of the battery can improve the energy density of the battery. The greater the silicon addition amount w, the greater the battery energy density, but the greater the volume expansion of the battery. At the same time, because the electronic conductivity of silicon is worse than that of graphite, the dynamics of the negative electrode sheet will deteriorate. The more silicon is added, the worse the dynamics, the poorer the fast charging performance, and the higher the temperature rise. In order to provide the dynamics of the silicon-doped negative electrode, the present invention adds cyclic organic matter and linear organic matter to the electrolyte, and adjusts the mass ratio a of the two to be in the range of 1.2-5, which can reduce the viscosity of the electrolyte, improve the wettability and dynamics of the silicon negative electrode, reduce lithium precipitation during high-rate charging and discharging, and thus alleviate the problem of poor dynamics of the negative electrode material caused by the increase in silicon addition, and improve the fast charging performance of the silicon-doped battery. At the same time, the present invention uses a shell to wrap the battery cell (such as a shell made of metal aluminum or an aluminum alloy), which has a certain impact resistance and rapid heat conduction ability, so that the battery can transfer heat during fast charging. At the same time, a connecting piece is used to connect the pole to the battery cell, thereby improving the current carrying capacity of the pole ear, reducing heat generation at the pole ear, further reducing the temperature rise of the battery, reducing the generation of side reactions, and improving the battery's cycle performance.

[0034] The present invention adjusts the silicon content w to 1%-40%, the mass ratio a of the cyclic organic matter to the linear organic matter to 1.2-5, and uses a shell and a connecting sheet in combination, so that the battery has the advantages of high energy density, good fast charging performance, and low temperature rise.

[0035] In some embodiments, Figure 1 As shown, the battery comprises a housing 1, the housing 1 comprises a first side surface and a second side surface which are arranged opposite to each other along the height direction of the housing 1, the first side surface is, for example, a top cover 11, and the second side surface is, for example, a bottom wall. As an embodiment, the top cover 11 may be provided along the first direction (i.e. Figure 1 A positive electrode column 12 and a negative electrode column 13 are disposed oppositely at both ends of the housing in the length direction, and a liquid injection hole 14 is also disposed on the top cover 11, and the liquid injection hole 14 is disposed between the positive electrode column 12 and the negative electrode column 13. Figure 2 and Figure 3 As shown, the housing 1 includes two battery cells 2 , and the two battery cells 2 are connected to the positive electrode column 12 and the negative electrode column 13 in the top cover 11 through the connecting piece 3 .

[0036] In some embodiments, the housing comprises aluminum or an aluminum alloy. For example, the housing is an aluminum shell, or an alloy of aluminum and other metals. The housing can be square, cylindrical, or other regular or irregular shapes.

[0037] In some embodiments, in the negative electrode active material, the mass proportion w of silicon element can be, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40% or any point value in the range of the above two point values, preferably w is 3%-25%. When the mass proportion of silicon element further meets the above range, it can prevent the problem of excessive volume expansion and poor kinetics of silicon-containing negative electrode caused by silicon-carbon material when improving the energy density of the battery.

[0038] In some embodiments, the silicon-based material includes at least one of silicon carbon SiC, silicon oxygen SiO, silicon alone, and silicon alloys, preferably SiC and / or SiO.

[0039] Exemplarily, in the negative electrode active material, the mass proportion of silicon element can be obtained by acid-treating the negative electrode active material and then performing ICP analysis and calculation. Alternatively, the test method for the mass proportion of silicon element can be tested by thermogravimetric analysis, for example, using Shimadzu DTG-60 thermogravimetric analyzer for testing, and the test conditions are: sample amount 5 mg, air as atmosphere, heating rate 10℃ / min from room temperature to 900℃ and constant temperature for 40min. The relationship between the mass proportion of silicon-carbon material (x) and the final weight residual percentage (y) of the entire test is: x=7y / 15. The mass proportion of silicon element can also be directly measured by EDS surface scanning the surface of the negative electrode sheet to measure the element content of Si as an auxiliary test method.

[0040] In some embodiments, the negative electrode active material further comprises a carbon-based material, and the carbon-based material comprises at least one of artificial graphite, natural graphite, hard carbon, and soft carbon. The mixed use of carbon-based materials and silicon-based materials can alleviate the problem of large volume expansion of silicon materials, improve the conductivity of negative electrode materials, improve the dynamics of negative electrode sheets, and increase the energy density of batteries.

[0041] In some embodiments, the mass ratio a of the linear organic matter and the cyclic organic matter satisfies: 1.2≤a≤5 (a=S2 / S1), for example, a can be 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 4.8, 5. The larger a is, the more linear organic matter is contained, and the better the kinetics of the electrolyte is; when a is greater than 5, the cyclic organic matter is too little to completely ionize the lithium salt to form separated ion pairs, resulting in decreased conductivity and decreased electrochemical performance of the battery; when a is less than 1.2, the cyclic organic matter is too much and the linear organic matter is too little, resulting in a larger viscosity of the electrolyte, a decreased ability to conduct lithium ions, and decreased electrochemical performance of the battery.

[0042] In some embodiments, the mass proportion of the cyclic organic matter is recorded as S1 based on the total mass of the electrolyte, and S1 satisfies: 1%≤S1≤30%. For example, S1 can be 1%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30% or any point value in the range composed of the above two point values, preferably 5%≤S1≤25%. Preferably, the cyclic organic matter includes C1-C8 cyclic carbonates, such as at least one of ethylene carbonate EC, propylene carbonate PC, butylene carbonate, and γ-butyl carbonate, preferably ethylene carbonate, which is conducive to the film formation of the negative electrode and can stabilize the negative electrode interface. Cyclic carbonates have a higher dielectric constant, which is conducive to the dissociation of lithium salts and improves the conductivity of the battery.

[0043] In some embodiments, the mass proportion of the linear organic matter is recorded as S2 based on the total mass of the electrolyte, and S2 satisfies: 30%≤S2≤80%, for example, S2 can be 30%, 40%, 50%, 60%, 70%, 80% or any point value in the range of the above two point values, preferably 40%≤S2≤70%. Preferably, the linear organic matter includes C1-C8 linear carbonates and / or C1-C8 linear carboxylates, for example, at least one of diethyl carbonate DEC, ethyl methyl carbonate EMC, dimethyl carbonate DMC, methyl propyl carbonate MPC, ethyl propyl carbonate EPC, dipropyl carbonate DPC, ethyl propionate EP, propyl propionate PP, and ethyl acetate EA. Compared with cyclic carbonates, C1-C8 linear carbonates and C1-C8 linear carboxylates have lower viscosity, can reduce the viscosity of the electrolyte, improve the dynamics of the battery, and are conducive to improving the fast charging performance of the battery.

[0044] In some embodiments, Figure 2 As shown, the connecting piece includes a positive connecting piece 31 and a negative connecting piece 32. The positive connecting piece 31 is connected to the positive electrode ear and the positive electrode column of the battery cell 2, and the negative connecting piece 32 is connected to the negative electrode ear and the negative electrode column of the battery cell 2.

[0045] In some embodiments, Figure 3 and Figure 4 As shown, one end of the positive electrode connecting piece 31 body is provided with two first pole ear connecting parts 311, and the first pole ear connecting part 311 is connected to the positive pole ear 21 of the battery cell 2; the other end of the positive electrode connecting piece 31 body includes a first pole column connecting part 312, and the first pole column connecting part 312 is protrudingly arranged on one side surface of the connecting piece body, and the first pole column connecting part 312 is used to connect with the positive pole 12 of the shell 1.

[0046] In some embodiments, Figure 3 and Figure 4 As shown, one end of the negative electrode connecting piece 32 body is provided with two second pole ear connecting parts 321, and the second pole ear connecting part 321 is connected to the negative pole ear 22 of the battery cell 2; the other end of the negative electrode connecting piece 32 body includes a second pole column connecting part 322, and the second pole column connecting part 322 is protrudingly arranged on one side surface of the negative electrode connecting piece 32 body, and the second pole column connecting part 322 is used to connect with the negative pole column 13 of the shell 1.

[0047] In some embodiments, the positive electrode connecting piece and the positive electrode ear, and the negative electrode connecting piece and the negative electrode ear are connected by welding, and the welding method can be ultrasonic welding, laser welding, etc.

[0048] In some embodiments, the positive electrode connecting piece and the positive electrode column, as well as the negative electrode connecting piece and the negative electrode column are also connected by welding, and the welding method can be ultrasonic welding, laser welding, etc.

[0049] In some embodiments, the material of the positive electrode connecting sheet is aluminum or an aluminum alloy, and the material of the negative electrode connecting sheet is copper or a copper alloy. Preferably, the materials of the positive electrode connecting sheet and the negative electrode connecting sheet are consistent with the positive electrode ear and the negative electrode ear, respectively, which is conducive to more stable welding and improves the connection stability between the connecting sheet and the electrode ear.

[0050] In some embodiments, Figure 3 and Figure 4 As shown, the portion where the positive electrode connecting sheet 31 is connected to the positive electrode column 12 is the first electrode column connecting portion 312, and the cross-sectional area of ​​the first electrode column connecting portion 312 is mmm 2 The part where the negative electrode connecting piece 32 is connected to the negative electrode column 13 is the second electrode column connecting portion 322, and the cross-sectional area of ​​the second electrode column connecting portion 322 is 0.8 mm to 1.2 mm. 2 The larger the m is, the larger the connection area between the connecting piece and the pole is, the better the electron conduction is, and the lower the internal resistance is.

[0051] In some embodiments, w, a and m satisfy: 0.03≤a / w≤5, 1.5≤m / w≤100, preferably, 0.2≤a / w≤0.8; 2≤m / w≤30.

[0052] a represents the ratio of the content of linear organic matter (linear carbonate and linear carboxylate) to the content of cyclic organic matter (cyclic carbonate) in the electrolyte, m is the cross-sectional area of ​​the first pole connection, and w is the amount of silicon doped in the negative electrode. Increasing w can increase the energy density of the battery, but it will make the volume expansion of the negative electrode more intense, aggravate the temperature rise of the battery, and lead to poor battery dynamics; as a increases, the content of linear organic matter increases, the lower the viscosity of the electrolyte, the better the ability of the electrolyte to transport lithium ions; an increase in the a / w value can alleviate the problem of poor battery dynamics caused by a large w, improve the battery dynamics, and reduce the temperature rise; if the a / w value is too small (less than 0.03), a is small and w is large, resulting in poor battery dynamics and a large temperature rise. If the a / w value is too large (greater than 5), a is large, resulting in too low a content of cyclic organic matter in the electrolyte, which cannot completely ionize the lithium salt to form separated ion pairs, resulting in a decrease in conductivity and a large internal resistance. The increase of m speeds up the transmission of electrons in the electrode, improves the conductivity, reduces the internal resistance, and reduces the temperature rise of the battery. The increase of m / w value can alleviate the problem of high battery temperature rise caused by large w.

[0053] In some embodiments, m satisfies: 60≤m≤200, preferably 80≤m≤150. That is, the cross-sectional area of ​​the first pole connection portion is 60 mm 2 -200 mm 2 , preferably 80mm 2 -150 mm 2 The cross-sectional area of ​​the second pole connection is 64mm 2 -240mm 2 .

[0054] In some embodiments, Figure 5 As shown, the pole connection part of the connecting piece is protrudingly arranged on one side surface of the connecting piece body, and the protruding dimension D is shown in the figure. The pole connection part is a cylindrical structure, and one end away from the connecting piece body is connected to the pole, and the interior is hollow. Preferably, the hollow part of the pole connection part is filled with laser welding protective glue to protect the welding mark between the pole connection part and the pole, and improve the connection stability between the connecting piece and the pole.

[0055] In some embodiments, the protrusion size D of the first pole connection portion and the second pole connection portion is independently 1 mm to 4 mm. When the protrusion size D is within the above range, on the one hand, the laser welding protective glue can be effectively filled to prevent the glue from falling off, and on the other hand, the protrusion position can be easily fitted with the welding position of the pole.

[0056] In some embodiments, Figure 4As shown, the positive electrode connecting sheet 31 is provided with a fuse unit between the first pole ear connecting portion 311 and the first pole column connecting portion 312, and the fuse unit is provided as a fuse zone 313, and the fuse zone 313 is arranged along the width direction of the positive electrode connecting sheet 31, and the fuse zone 313 is provided between the first pole ear connecting portion 311 and the first pole column connecting portion 312. A fuse notch is provided on both sides of the fuse zone 313, and the two fuse notches and the fuse zone are located on the same straight line to reduce the cross-sectional area of ​​the current passing through the fuse unit, and when a short circuit occurs in the battery or the current is too large, the fuse unit is more likely to be melted, thereby avoiding safety hazards.

[0057] In some embodiments, in order to improve the conductivity of the electrolyte, the electrolyte also includes a lithium salt, and the lithium salt includes one or more of lithium hexafluorophosphate LiPF6, bis(fluorosulfonyl)imide lithium salt LiFSI, bis(trifluoromethylsulfonyl)imide lithium salt LiTFSI, lithium difluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorooxalatophosphate, lithium tetrafluoroborate and lithium tetrafluorooxalatophosphate.

[0058] In some embodiments, the electrolyte includes lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate; based on the total mass of the electrolyte, the mass proportion of lithium hexafluorophosphate is recorded as L1%, and the mass proportion of lithium bis(fluorosulfonyl)imide is recorded as L2%; L1 satisfies: 2%≤L1≤20%, and L1 can be, for example, 3%, 5%, 8%, 10%, 12%, 15%, 16%, 18%, 20% or any point value in the range of the above two point values, preferably 5%≤L1≤15%. L2 satisfies: 0.1%≤L2≤20%, and L2 can be, for example, 0.1%, 1%, 2%, 3%, 5%, 8%, 10%, 12%, 15%, 16%, 18%, 20% or any point value in the range of the above two point values, preferably 1%≤L2≤15%. Compared with lithium hexafluorophosphate LiPF6, lithium bis(fluorosulfonyl)imide salt LiFSI has a larger anion group, and the anion group has a smaller binding energy to lithium ions. When the two lithium salts are in the same concentration in the electrolyte, lithium bis(fluorosulfonyl)imide salt LiFSI has higher conductivity and lithium ion migration number; in addition, LiPF6 is easily decomposed into LiF and PF5 at high temperature in carbonate solvents, resulting in increased side reactions of the battery, while LiFSI has higher thermal stability in the electrolyte than LiPF6; the use of a mixed lithium salt of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate can improve the conductivity of the electrolyte, further improve the kinetic properties of the electrolyte, and improve the thermal stability of the electrolyte.

[0059] In some embodiments, L2 and L1 satisfy: 8%≤L1+L2≤25%, and the value of L1+L2 can be, for example, 8%, 10%, 12%, 14%, 15%, 18%, 20%, 22%, 25% or any point value in the range composed of the above two point values. If the total content of the two lithium salts is less than 8%, the lithium salt concentration is low, resulting in low conductivity of the electrolyte; if the total content of the two lithium salts is higher than 25%, the viscosity of the electrolyte increases, and at the same time, the anions enter the lithium ion solvation structure to form contact ion pairs, the number of independent lithium ions decreases, and the conductivity of the electrolyte also decreases. When the total content of the two lithium salts of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate is adjusted to the above range, the conductivity of the electrolyte is higher under the same solvent system.

[0060] In some embodiments, L=L2 / L1, L satisfies: 0.05≤L≤2.5, and the ratio L of L2 / L1 can be, for example, 1, 1.2, 1.5, 1.6, 1.8, 2, 2.2, 2.5, 2.8, 3, or any point value in the range of the above two point values. If L2 / L1>2.5, there is too little lithium hexafluorophosphate in the electrolyte, and the HF generated by its decomposition is insufficient to react with the aluminum current collector to form an AlF3 passivation layer, and the positive electrode current collector cannot be effectively passivated, causing the electrolyte to produce gas on the aluminum current collector, causing battery expansion; if L2 / L1<0.05, the content of lithium bis(fluorosulfonyl)imide is too little, and the conductivity and thermal stability of the electrolyte cannot be effectively improved. Adjusting the mass ratio of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate to meet the above range can ensure the passivation of the positive electrode current collector and improve the kinetics and thermal stability of the electrolyte.

[0061] In some embodiments, in order to further enhance the passivation of the positive electrode current collector, the positive electrode current collector uses a composite aluminum foil. The composite aluminum foil includes an intermediate layer and an aluminum coating disposed on the surfaces of both sides of the intermediate layer. The intermediate layer includes polymer materials such as PET, PP, and PI. The thickness of the aluminum coating can be 0.5μm-2μm. The aluminum coating on the surface of the composite aluminum foil can enable LiPF6 to generate an AlF3 passivation layer on its surface, thereby enhancing the passivation effect of the positive electrode current collector. In addition, the use of composite aluminum foil can reduce the mass of the positive electrode sheet and increase the energy density of the battery on the one hand, and also improve the safety of the battery on the other hand. When the current is overloaded, the local temperature is high, and the polymer in the composite aluminum foil will melt, thereby interrupting the electronic path and reducing the risk of battery combustion and explosion.

[0062] In some embodiments, in order to further improve the fast charging performance of the battery, the battery cell includes multiple positive ears and multiple negative ears, the positive ears and the negative electrode sheets are connected to the battery cell, and the positive ears and the negative electrode sheets protrude from one side of the battery cell. The multi-ear design enables the battery to have multiple interfaces connecting the internal and external circuits of the battery. These interfaces serve as channels for current flow, and the increase in their number directly increases the current capacity of the battery. During the fast charging process, more current can flow into or out of the battery through these interfaces at the same time, significantly speeding up the charging or discharging speed of the battery and improving the fast charging performance of the battery.

[0063] In some embodiments, Figure 6 As shown, a plurality of positive pole ears 21 and a plurality of negative pole ears 22 are arranged on one side of the wound cell monomer 2, and the plurality of positive pole ears 21 and the plurality of negative pole ears 22 are stacked, that is, the projections of the plurality of positive pole ears in the thickness direction of the cell overlap, and the projections of the plurality of negative pole ears in the thickness direction of the cell overlap. The plurality of positive pole ears are connected to the first pole ear connection portion of the positive electrode connecting sheet (for example, by welding), and the plurality of negative pole ears are connected to the second pole ear connection portion of the negative electrode connecting sheet (for example, by welding).

[0064] In some embodiments, the positive electrode ear is made of aluminum, i.e., a positive electrode soft electrode ear; the negative electrode ear is made of copper, i.e., a negative electrode soft electrode ear. The positive electrode ear and the negative electrode sheet can be punched out by the positive electrode collector and the negative electrode collector, respectively, or can be firmly connected to the positive electrode sheet and the negative electrode sheet by welding or other connection methods, respectively. For example, the positive electrode soft electrode ear is welded to the composite aluminum foil by roll welding.

[0065] In some embodiments, the single layer thickness of the positive electrode ear is dμm, and d satisfies: 5≤m≤15. The single layer thickness d of the positive electrode ear can be, for example, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, or any point value in the range of the above two point values. The single layer thickness of the negative electrode ear is 0.8d-dμm, and the single layer thickness d of the negative electrode ear can be, for example, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, or any point value in the range of the above two point values. If the single layer thickness of the pole ear is too small, the current carrying capacity will decrease, which will easily lead to heat generation at the pole ear; if the single layer thickness of the pole ear is too large, the mass will increase, which will reduce the energy density of the battery. When the single-layer thickness of the positive electrode ear and the negative electrode ear is adjusted within the above range, it is possible to avoid excessive temperature rise of the electrode ear, reduce the temperature rise of the battery and take into account the energy density of the battery.

[0066] "Single-layer thickness" refers to the thickness of one layer of tabs when multiple positive electrode sheets are stacked.

[0067] In some embodiments, d, L1, and L2 satisfy: 5≤L+d≤18, and the value of L+d can be, for example, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 or any point value in the range formed by any two of the above point values, preferably 8≤L+d≤12.

[0068] The larger the L+d formula value is, the greater the LiFSI content is, the higher the migration number of lithium salt in the electrolyte is, the larger d is, the current carrying capacity of the pole ear is enhanced, and the temperature rise of the battery is lower; when the L+d formula value is too large, exceeding 18, it will lead to incomplete passivation at the pole ear, causing the electrolyte to easily decompose and produce gas; when the L+d formula value is too small, less than 5, the LiPF6 content is too low, resulting in the inability to effectively passivate the positive electrode collector, causing the electrolyte to produce gas on the positive electrode collector, causing the battery to expand; when d is too small, it will cause heat generation at the pole ear and fail to effectively reduce the temperature rise.

[0069] In some embodiments, the capacity of the battery is recorded as C Ah, where C satisfies: 100≤C≤300, more preferably 100≤C≤300, preferably 120≤C≤250. The battery has a high energy density, which can help alleviate "energy replenishment anxiety".

[0070] In some embodiments, the OI value of the negative electrode sheet is recorded as I, and I satisfies: 10≤I≤20. The OI value of the negative electrode sheet can be, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or any point value in the range composed of the above two point values. The OI value of the negative electrode sheet is the ratio of the 004 peak to the 110 peak area in the XRD test of the negative electrode sheet. The smaller the OI value of the negative electrode sheet, the stronger the anisotropy, the more active sites in the negative electrode active material particles, and the better the kinetic performance of the negative electrode sheet. However, when the OI value is too small, less than 10, the negative electrode active material has more active sites, and more negative electrode film-forming additives are needed to form a stable interface. When the additives are insufficient, the electrolytic interface will be unstable, and more film-forming substances are needed to protect the interface.

[0071] The test method of the OI value of the negative electrode sheet includes: taking out the negative electrode sheet, cleaning it with dimethyl carbonate, drying it at 60°C, then measuring the XRD diffraction peak of the negative electrode sheet by XRD, and finally calculating the ratio of I(004) / I(110).

[0072] In some embodiments, the electrolyte further comprises a fluorine-containing additive, and the mass proportion of the fluorine-containing additive is recorded as S3 based on the total mass of the electrolyte, and S3 satisfies: 0.1%≤S3≤20%, and the mass proportion of the fluorine-containing additive S3 can be, for example, 0.1%, 1%, 2%, 3%, 5%, 8%, 10%, 12%, 15%, 16%, 18%, 20% or any point value in the range of the above two point values. Fluorine-containing additives rich in F elements need to be added to the electrolyte. The lowest unoccupied orbital LUMO (Lowest Unoccupied Molecular Orbital) of the fluorine-containing additive is low and easy to be reduced, which is conducive to the formation of an interface rich in inorganic LiF on the surface of the negative electrode. The inorganic substance has a large mechanical strength, can inhibit the expansion of silicon particles, and reduce the formation of new interfaces. In addition, fluoride is usually easy to undergo reduction reaction at the negative electrode. Once a new interface is generated at the negative electrode, the fluoride will immediately react to form a stable interface, thereby improving the stability of the negative electrode interface.

[0073] In some embodiments, the fluorine-containing additive includes at least one of fluorinated carbonate, fluorinated carboxylate, fluorinated ether, fluorinated phosphate, and fluorinated phosphazene. Specifically, the fluorine-containing additive includes one or more of fluoroethylene carbonate FEC, trifluoromethylethylene carbonate FPC, methyl trifluoroethyl carbonate FEMC, difluoroethyl acetate DFEA, ethoxy pentafluorocyclotriphosphazene PFPN, and phenoxy pentafluorocyclotriphosphazene HFPN, preferably fluoroethylene carbonate FEC.

[0074] In order to further improve the long cycle performance of the battery, it is necessary to have sufficient film-forming additives to stabilize the interface of the negative electrode active material. The present invention has found that the content S3 of the fluorine-containing additives in the electrolyte, the content S1 of the cyclic organic matter and the OI value I of the negative electrode sheet can be adjusted to meet the following conditions: 0.05≤S1 / I≤3, 0.01≤S3 / I≤2, which can achieve the long cycle performance of the battery. Both fluorine-containing additives and ethylene carbonate EC in cyclic organic matter can form a film at the negative electrode, but the film-forming effect of EC is not as good as that of fluorine-containing additives. Fluorine-containing additives can form a LiF-rich SEI film at the negative electrode, especially at the silicon-doped negative electrode. Fluorine-containing additives can greatly improve the cycle performance of the battery. When the fluorine-containing additives, cyclic organic matter and the negative electrode sheet OI value are controlled to meet the above formula, the cycle performance of the battery can be greatly improved. When S1 / I and S3 / I are too small, the content of fluorine-containing additives and cyclic organic matter is low, resulting in the inability to form a stable interface at the negative electrode, causing the battery performance to decline. When S1 / I and S3 / I are too large, the content of fluorine-containing additives is relatively high, and it is easy to defluorinate at high temperature to produce HF corrosion interface, causing the battery to produce gas. The high content of cyclic organic matter ethylene carbonate will also cause it to oxidize and decompose at the positive electrode to produce gas.

[0075] When calculating the S1 / I and S3 / I formulas, directly substitute the numerical values ​​for S1 and S3 without substituting %. For example, when S1=10%, I=10, and S3=10%, S1 / I=10 / 10=1, and S3 / I=10 / 10=1.

[0076] In order to reduce the problem of gas production at the negative electrode by fluorine-containing additives and cyclic organic matter ethylene carbonate, in some embodiments, the electrolyte also includes a sulfur-containing additive, and the mass proportion of the sulfur-containing additive is recorded as S4 based on the total mass of the electrolyte; S4 satisfies: 0.1%≤S4≤5%. The mass proportion S4 of the sulfur-containing additive can be, for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%. Sulfur-containing additives are added to the electrolyte, and the sulfur-containing additives generate a stable interface at the active sites on the positive electrode surface with higher oxidizability, preventing the solvents in the electrolyte that are prone to gas production, such as ethylene carbonate, from reacting at the active sites to produce gas, thereby effectively improving the high-temperature cycle performance of the battery. When the content of the sulfur-containing additive is controlled within the above range, it can be avoided that too much sulfur-containing additive will cause the battery impedance to be large and the kinetics to decrease.

[0077] In some embodiments, the sulfur-containing additive includes at least one of vinyl sulfate DTD, vinyl sulfite, 1,3-propane sultone PS, 1,3-propene sultone PST, methylene methane disulfonate, and thiophene, preferably 1,3-propane sultone.

[0078] In some embodiments, the positive electrode sheet includes a positive electrode active material, the chemical formula of the positive electrode active material includes LiNi x Co y Mn z M k O2, M includes one or more of Fe, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V, Ti, wherein 0.7≤x≤1, 0≤y≤1, 0≤z≤1, 0≤k≤0.05, and 0≤x+y+z≤1, preferably 0.8≤x≤0.94. The particle morphology of the positive electrode active material has a polycrystalline morphology and / or a single crystal morphology. The positive electrode active material has a higher Ni content, can exert a higher capacity, and improve the energy density of the battery. However, the higher the Ni content, the more unstable the positive electrode active material is, and it will oxidize the electrolyte to produce a large amount of gas, and the greater the battery expansion.

[0079] In order to take into account both the high temperature performance and the dynamic performance of the battery, and to prevent the battery from expanding at high temperatures. The present invention adjusts the content S1 of the cyclic organic matter (cyclic carbonate), the nickel content x of the positive electrode active material, and the content S4 of the sulfur-containing additive to meet the following conditions: 0.05≤S4 / S1≤5, 0.1≤S4 / x≤7 (preferably 0.05≤S4 / S1≤1, 0.8≤S4 / x≤4), which can achieve good cycle performance, high temperature performance and dynamic performance in the ternary silicon-doped system. When calculating S4 / x, S4 is directly substituted into the numerical value without substituting into %, for example, S4=2%, when x=1, S4 / x=2 / 1=1.

[0080] Cyclic carbonates are prone to catalytic oxidation on the surface of the positive electrode, causing serious gas production in the electrolyte. The more cyclic carbonates there are, that is, the larger S1 is, the easier it is for the electrolyte to produce gas; the higher the Ni content of the positive electrode material, that is, the larger the x is, the more serious the gas production is; and the sulfur-containing additive can form a film on the positive electrode to protect the positive electrode and prevent the cyclic carbonate from continuing to undergo oxidation reaction at the positive electrode. When the cyclic carbonate content S1 increases, the sulfur-containing additive content S4 also increases accordingly, which can reduce the gas production caused by the increase in the cyclic carbonate content and reduce battery expansion; when the nickel content x in the positive electrode material increases, the electrolyte gas production is more serious, and the sulfur-containing additive content S4 increases, which can inhibit the electrolyte gas production and reduce battery expansion. When adjusting 0.05≤S4 / S1≤5, 0.1≤S4 / x≤7 within the above range, it can take into account both the high temperature performance and kinetic performance of the battery and reduce the high temperature expansion of the battery.

[0081] In some embodiments, the electrolyte includes a lithium salt additive; based on the total mass of the electrolyte, the mass of the lithium salt additive accounts for 0.1-3%. The lithium salt additive includes one or more of lithium difluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorobis(oxalatophosphate), lithium tetrafluoroborate, lithium nitrate, and lithium tetrafluorooxalatophosphate. The lithium salt additive can form a stable interface between the positive and negative electrodes, which is beneficial to improving the high and low temperature performance of the battery.

[0082] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer located on at least one side of the positive electrode current collector. The positive electrode active layer is not particularly limited, and the positive electrode active layer may include components such as a positive electrode active material, a conductive agent, and a binder according to conventional compositions in the art. The positive electrode active material includes the above-mentioned positive electrode active materials. Among them, components such as conductive agents and binders may be selected from conventional materials in the art, and the conductive agent may be selected from one or more of conductive carbon black, carbon nanotubes, conductive graphite, and graphene, and the binder may be selected from one or more of polyvinylidene fluoride (PVDF), acrylic acid-modified PVDF, polyacrylate polymers, polyimide, styrene-butadiene rubber, and styrene-acrylic rubber.

[0083] In some embodiments, the battery is a lithium ion battery.

[0084] In some embodiments, the battery is a wound lithium-ion battery.

[0085] In some embodiments, the battery is a lithium-ion secondary battery, for example, a power lithium battery, a consumer lithium battery, or an energy storage lithium battery.

[0086] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0087] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0088] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0089] The batteries of the examples and comparative examples of the present invention were prepared according to the following preparation method, and the differences from Example 1-1 are shown below.

[0090] Example 1-1

[0091] (1) Preparation of electrolyte:

[0092] In a glove box filled with argon (H2O < 0.1ppm, O2 < 0.1ppm), the cyclic organic solvent EC and the linear organic solvent EMC were mixed evenly in a mass ratio of 15 / 60, and then 12.5% ​​LiFSI and 6.5% LiPF6 based on the total mass of the electrolyte were added thereto. After dissolution, 2% FEC (fluorine-containing additives), 1% PS (sulfur-containing additives), 1.5% vinylene carbonate VC, 1% LiPO2F2, and 0.5% LiBOB were added based on the total mass of the electrolyte. The mixture was stirred evenly, and the electrolyte was obtained after passing the moisture and free acid tests.

[0093] (2) Preparation of positive electrode sheet:

[0094] The ternary material (LiNi 0.9 Co 0.03 Mn 0.05 M 0.02O2) powder, polyvinylidene fluoride and acetylene black are put into a vacuum mixer in a mass ratio of 96:2.5:1.5, and N-methylpyrrolidone (NMP) is added. The mixture is fully mixed under the action of the vacuum mixer until a uniform and fluid positive electrode slurry is formed, wherein the solid content is 55wt%; the positive electrode slurry is evenly coated on a composite aluminum foil (10μm PET + 1μm aluminum coating on both sides) with a thickness of 12μm, and the coating single-side surface density is 16.5mg / cm 2 , compacted density 3.44g / cm 3 After drying, rolling, slitting and punching, the positive electrode sheet is obtained.

[0095] (3) Preparation of negative electrode sheet:

[0096] Graphite, SiO, styrene-butadiene rubber, sodium carboxymethyl cellulose and acetylene black were put into a vacuum mixer in a mass ratio of 86.85:9.65:1.45:1.05:1, and deionized water was added. The mixture was fully mixed under the action of the vacuum mixer to finally form a uniform negative electrode slurry with good fluidity, wherein the solid content was 45wt%; the negative electrode slurry was evenly coated on a copper foil with a thickness of 6μm, and the coating single-side surface density was 10mg / cm 2 , compacted density 1.6g / cm 3 , drying, rolling and die-cutting to obtain the negative electrode sheet.

[0097] (4) Preparation of batteries:

[0098] The positive electrode sheet obtained in the step, the negative electrode sheet obtained in the step and the isolation film (PP, double-sided ceramic, water-based glue) are wound to obtain a bare battery cell; the tabs of the two bare battery cells are welded to the connecting sheet and then placed in a battery casing, and the electrolyte prepared in the step is injected into the dried and qualified battery cell, and a battery is obtained after standing, aging, formation, exhaust, aging, sorting and other processes.

[0099] Testing the battery

[0100] (1) Impedance test

[0101] The battery was discharged at a rate of 1.0C to the discharge termination voltage, then charged at a rate of 1.0C to the charge limit voltage, discharged at 1.0C to the discharge termination voltage, and C0 was recorded. The battery was charged at 1.0C constant current and constant voltage to the charge limit voltage, discharged at 1.0C to 50% SOC, left to stand for 4 hours, and the battery voltage V1 was recorded. The battery was discharged at 3C current for 10s, and the discharge end voltage V1 and the discharge current I were recorded. The discharge impedance of the battery was calculated to be R = (V1-V2) / I*1000mΩ.

[0102] (2) High temperature cycle performance test

[0103] High temperature cycle performance test: At 45°C, use a vernier caliper to measure the thickness d1 of the battery before cycling, charge the divided battery to 4.25V at 1C constant current and constant voltage, with a cut-off current of 0.05C, and then discharge it to 2.75V at 1C constant current. Repeat this cycle. After 800 cycles of charge and discharge, calculate the capacity retention rate at the 800th week, and record the battery thermal thickness d2 at the same time. The calculation formula is as follows:

[0104] The 800th cycle capacity retention rate (%) = (800th cycle discharge capacity / first cycle discharge capacity) × 100%.

[0105] The battery expansion rate at the 800th cycle (%) = (battery thickness d2 at the 800th cycle / battery thickness d1 before the cycle) × 100%.

[0106] (3) Temperature rise test

[0107] At 25°C, three temperature sensors are placed at the center of the battery, the positive pole ear, and the negative pole ear to monitor the real-time temperature. The divided battery is charged to 3.65V at 1C constant current and constant voltage, with a cut-off current of 0.05C, and then discharged to 2.5V at 1C constant current, and the initial discharge capacity C0 is recorded. The battery is discharged to 20% SOC at 1C, and after standing for 4 hours, the average temperature T0 of the temperature sensor is recorded. The battery is then charged to 80% SOC at a rate of 4C, and the real-time maximum temperature T1 during the charging process is recorded, and the temperature rise T1-T0 is calculated.

[0108] Example 1-3, and Comparative Examples 1-3 are carried out with reference to Example 1-1, and the main differences are shown in Table 1. Among them, in Example 1, the mass proportion w of the silicon element in the negative electrode active material is changed. In Example 2, the cross-sectional area m of the first pole connecting portion is changed. In Example 3, the mass ratio a of linear organic matter and cyclic organic matter is changed. In Comparative Example 1, the value of w is too large and the value of a is too small, which are not within the protection scope of the present invention. In Comparative Example 2, the value of w is too small, which is not within the protection scope of the present invention. In Comparative Example 3, the value of a is too large, which is not within the protection scope of the present invention.

[0109] Table 1

[0110]

[0111]

[0112] The performance data of the battery tests obtained in the above Example 1-3 and Comparative Examples 1-3 are recorded in Table 2.

[0113] Table 2

[0114]

[0115] As can be seen from Table 2, the invention can improve the fast charging performance of silicon-doped batteries by adding cyclic organic matter and linear organic matter to the electrolyte and adjusting the mass ratio a of the two to be in the range of 1.2-5. At the same time, the use of a connecting sheet to connect the pole to the battery cell can reduce the temperature rise of the battery, reduce the battery expansion, and improve the cycle performance of the battery.

[0116] The Example 4 and Example 5 groups were carried out in accordance with Example 1-1, and the main differences are shown in Table 3. In the Example 4 group, the value of L was changed by adjusting the LiPF6 content L1 and the LiFSI content L2 in the electrolyte. In the Example 5 group, the single layer thickness d of the positive electrode ear was changed.

[0117] Table 3

[0118]

[0119] It can be seen from Table 3 that the present invention can improve the capacity retention rate of the battery and reduce the expansion rate of the battery by adjusting the value ranges of L1, L2, L2 / L1 and L1+L2 within the protection scope of the present invention. In addition, when the value of L+d is within the protection scope of the present invention, the expansion rate and temperature rise of the battery can be reduced.

[0120] The examples 6 to 8 were carried out with reference to the examples 1-1, and the main differences are shown in Table 4. Among them, the values ​​of L and L1+L2 were changed by adjusting the LiPF6 content L1 and the LiFSI content L2 in the electrolyte in the examples 6 to 8.

[0121] Table 4

[0122]

[0123] It can be seen from Table 4 that the present invention can improve the fast charging cycle performance of the battery and reduce the expansion rate of the battery by adjusting the value ranges of L1, L2, L, and L1+L2 within the protection scope of the present invention.

[0124] The experiments of Example 9 and Example 10 were carried out in accordance with Example 1-1, and the main differences are shown in Table 5. In Example 9, the content of the fluorine-containing additive was changed by S3. In Example 10, the OI value of the negative electrode sheet was changed.

[0125] Table 5

[0126]

[0127] It can be seen from Table 5 that when the content of fluorine-containing additives and the value of S3 / I are within the protection scope of the present invention, the stability of the negative electrode interface can be improved, the capacity retention rate of the battery can be improved, and the battery expansion can be reduced. When the value of S1 / I is within the protection scope of the present invention, the capacity retention rate of the battery can be improved and the battery expansion can be reduced.

[0128] The experiments of Example 11 and Example 12 were carried out in accordance with Example 1-1, and the main differences are shown in Table 6. In Example 11, the content of Ni in the positive electrode active material was changed. In Example 12, the content of S4 in the sulfur-containing additive was changed.

[0129] Table 6

[0130]

[0131] It can be seen from Table 6 that when the Ni content of the positive electrode active material, the cyclic carbonate content S1, the sulfur-containing additive content S4, and the values ​​of S4 / S1 and S4 / x are within the protection scope of the present invention, the high temperature performance and kinetic performance of the battery can be taken into account and the high temperature expansion of the battery can be reduced.

[0132] The Example 13 group was carried out with reference to the Example 1-1, and the main differences are shown in Table 7. Among them, the capacity C of the battery was changed in the Examples 13-1 and 13-2, and the silicon-based material was changed in the Example 13-3.

[0133] Table 7

[0134]

[0135] It can be seen from Table 7 that the battery of the present invention has a higher energy density, which can help alleviate "energy replenishment anxiety".

[0136] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0137] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A battery, characterized in that: The battery comprises: At least one battery cell, wherein the battery cell comprises a positive electrode tab and a negative electrode tab; The connecting piece comprises a connecting piece body, a pole connecting portion arranged at one end of the connecting piece body, and a pole ear connecting portion arranged on the connecting piece body; the pole connecting portion is protrudingly arranged on the connecting piece body; A shell, encapsulating the battery cell and the connecting piece; The battery cell comprises a stacked positive electrode sheet, a separator and a negative electrode sheet; the negative electrode sheet comprises a negative electrode active material, and the negative electrode active material comprises a silicon-based material; in the negative electrode active material, the mass proportion w of silicon element is 1%-40%; The battery also includes an electrolyte, the electrolyte includes cyclic organic matter and linear organic matter; the cyclic organic matter includes C1-C8 cyclic carbonate; the linear organic matter includes C1-C8 linear carbonate and / or C1-C8 linear carboxylate; the mass ratio of the linear organic matter to the cyclic organic matter is denoted as a, and a satisfies: 1.2≤a≤5.

2. The battery according to claim 1, characterized in that The connecting piece includes a positive connecting piece and a negative connecting piece; the shell includes a top cover, and the top cover is provided with a positive electrode column and a negative electrode column opposite to each other at two ends along the first direction of the shell; Preferably, the positive electrode connecting sheet comprises: a first pole ear connecting portion, the first pole ear connecting portion is connected to the positive pole ear of the battery cell; a first pole post connecting portion, the first pole post connecting portion is connected to the positive pole post of the shell; Preferably, the negative electrode connecting sheet comprises: a second pole ear connecting portion, the second pole ear connecting portion is connected to the negative pole ear of the battery cell; a second pole post connecting portion, the second pole post connecting portion is connected to the negative pole post of the shell; Preferably, the cross-sectional area of ​​the first pole connecting portion is mm 2 , and / or, the cross-sectional area of ​​the second pole connection portion is 0.8 mm-1.2 mm 2 ; Preferably, m satisfies: 60≤m≤200; Preferably, w, a and m satisfy: 0.03≤a / w≤5, 1.5≤m / w≤100; Preferably, the protruding dimension D of the first pole connecting portion is 1 mm-4 mm; and / or the protruding dimension D of the second pole connecting portion is 1 mm-4 mm.

3. The battery according to claim 1, characterized in that The mass proportion of the cyclic organic matter is recorded as S1 based on the total mass of the electrolyte, and S1 satisfies: 1%≤S1≤30%; And / or, based on the total mass of the electrolyte, the mass proportion of the linear organic matter is recorded as S2, and S2 satisfies: 30%≤S2≤80%; And / or, the cyclic organic matter includes at least one of ethylene carbonate, propylene carbonate, butylene carbonate, and γ-butyl carbonate; And / or, the linear organic matter includes at least one of diethyl carbonate, ethyl methyl carbonate, dimethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, dipropyl carbonate, ethyl propionate, propyl propionate and ethyl acetate.

4. The battery according to claim 1, characterized in that The electrolyte comprises lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate; based on the total mass of the electrolyte, the mass proportion of lithium hexafluorophosphate is 11%, and the mass proportion of lithium bis(fluorosulfonyl)imide is 12%; L1 satisfies: 2% ≤ L1 ≤ 20%; and / or, L2 satisfies: 0.1% ≤ L2 ≤ 20%; Preferably, L2 and L1 satisfy: 8%≤L1+L2≤25%; Preferably, L=L2 / L1, and L satisfies: 0.05≤L≤2.

5.

5. The battery according to claim 4, characterized in that The battery cell comprises a plurality of positive tabs and a plurality of negative tabs; the single layer thickness of the positive tab is d μm; and / or the single layer thickness of the negative tab is 0.8 d-d μm; preferably, d satisfies: 5 ≤ m ≤ 15; Preferably, d, L1, and L2 satisfy: 5≤L+d≤18.

6. The battery according to claim 1, characterized in that The OI value of the negative electrode sheet is denoted as I, where I satisfies: 10≤I≤20; Preferably, the capacity of the battery is denoted as C Ah, where C satisfies: 100≤C≤300, more preferably 100≤C≤300.

7. The battery according to claim 6, characterized in that The electrolyte further includes a fluorine-containing additive, and the mass proportion of the fluorine-containing additive is denoted as S3 based on the total mass of the electrolyte, and S3 satisfies: 0.1%≤S3≤20%; Preferably, S1, S3 and I satisfy: 0.05≤S1 / I≤3, 0.01≤S3 / I≤2; Preferably, the fluorine-containing additive includes at least one of fluorinated carbonates, fluorinated carboxylates, fluorinated ethers, fluorinated phosphates, and fluorinated phosphazenes.

8. The battery according to claim 3, characterized in that The electrolyte further includes a sulfur-containing additive, and the mass proportion of the sulfur-containing additive is recorded as S4 based on the total mass of the electrolyte; S4 meets: 0.1% ≤ S4 ≤ 5%; Preferably, the sulfur-containing additive includes at least one of vinyl sulfate, vinyl sulfite, 1,3-propane sultone, 1,3-propylene sultone, methylene methane disulfonate, and thiophene.

9. The battery according to claim 8, characterized in that The positive electrode sheet includes a positive electrode active material, the chemical formula of which includes LiNi x Co y Mn z M k O2, M includes one or more of Fe, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V, Ti, wherein 0.7≤x≤1, 0≤y≤1, 0≤z≤1, 0≤k≤0.05, and 0≤x+y+z≤1; S1, S4 and x satisfy: 0.05≤S4 / S1≤5, 0.1≤S4 / x≤7.

10. The battery according to any one of claims 1 to 9, characterized in that: The electrolyte includes a lithium salt additive; based on the total mass of the electrolyte, the mass of the lithium salt additive accounts for 0.1-3%; Preferably, the lithium salt additive includes one or more of lithium difluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorobis(oxalatophosphate), lithium tetrafluoroborate, lithium nitrate, and lithium tetrafluorooxalatophosphate; Preferably, the silicon-based material includes at least one of silicon carbon, silicon oxygen, silicon element, and silicon alloy; Preferably, the negative electrode active material further comprises a carbon-based material, and the carbon-based material comprises at least one of artificial graphite, natural graphite, hard carbon and soft carbon.